Needs Analysis for the Development of Student Worksheets on Heat Material in the Context of a Solar Energy Desalinator - Aniliawati, Ur; Wardana, Rendy Wikrama; Mayub, Afrizal (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Before using student worksheets, so that they can be used legally, they should be tested first on at least 3 experts and tested on students. The type of research used is descriptive qualitative. This needs analysis aims to determine what teaching materials are needed in the heat material at Junior High School 4 Bengkulu City. The method in this study, researchers used the Research and Development (R&D). ADDIE model development procedure. The research was carried out in September 2022. The research sample consisted of 40 students who were in 8th grade. The research instruments were in the form of interviews and student response questionnaires which consisted of 18 question items regarding the needs of integrated worksheets for solar energy-based desalinator designs which contained 4 aspects namely indicator aspects, teaching material needs aspects, learning media aspects, and interest aspects. The results of student response data based on aspects of the average indicator of 80% do not use Student Worksheets on heat material, the aspect of teaching material needs on average is 80% of students find it difficult to learn science on heat material with teaching materials that used by teachers, the learning media aspects of students on average 77% rarely use laboratories to conduct experiments or practicums, so teachers rarely use and provide Student Worksheets to students in science lessons, and the motivational aspects of student interest on average on average 82% are quite interested, quite enthusiastic about learning science so what are they interested in developing Student Worksheets teaching materials. From the data obtained, some students agree that it is necessary to develop Student Worksheets